RSA Highlights: News and reports from the RSA community: Revitalising Lagging Regions: How to improve the EU's Innovation Programme. Issue 5 (November 2019) - Barzotto, Mariachiara; Corradini, Carlo; Labory, Sandrine; Fai, Felicia; Tomlinson, Phil
No abstract available